Relationship between oral health status, inadequate nutrition intake and underweight among elderly living in Pondok in Kelantan. - Hamid, Abdul Manaf Hj (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2007)
Introduction: The relationship between oral health status and nutritional status among elderly people have been explored by various researchers. However the exact nature and strength of the relationship has not been fully described. Objectives:· This cross-sectional study were to investigate the dentition status, prosthetic needs and functional oral status of elderly people, to assess the nutrient intake, to determine the distribution of body mass index, to determine correlation between daily calorie intake and body mass index and to investigate the association between functional oral status with inadequate calorie intake and underweight in elderly people living in "Pondok" in Kelantan. Methodology: A cross-sectional study was conducted from Jun 2004 to January 2005, and a simple random sampling was utilized for selection of 386 subjects. Subjects were interviewed using a structured form to collect information about the subjects' demographic background and self-reported health status: For the anthropometric measurement; the subjects' weight and height were measured, then, body mass 'index was calculated. The 24-hour recall method -was used to provide information on the subject's e~act food intake during the pre.v ious 24 hours. Finally, it was followed by oral examination whereby the assessment of natural ·. teeth and prosthetic status were done. The "Nutrical Software" was used for nutrient calculation I followed by SPSS version 11.5 for data analysis. Results: The response rate was 95.6% and majority of the respondents were fem~le (92.4 %) .. The percentage of edentulism was 81.0% (95% CJ: 77.0, 85.0) with high prosthetic need, 47.2% (95% Cl: 42.1, 52.3). Compromised functional oral status was experienced by 48.2% (95% Cl: 43;1, 53.3) of the subjects. Majority was contributed by edentate elderly without (23.6%) or with defective dentures (56.2%). Regarding nutritional status I 70.7 % (95% Cl: 66.1, 75.3) of the subjects had inadequate calorie intake, that is less than 66. 7o/o or 2/3 of the Recommended Nutrient Intake (RNI) and 25.7 % (95% Cl: 21.2, 30.2) were underweight. The od~s of having inadequate calorie intake and getting underweight among elderly with a compromised functional oral status was 3. 7 times and 42.0 times respectively, compared to non-compromised functional oral status. Conclusion: This study· has shown that dentition status of elderly living in "Pondok" in Kelantan was not satisfactory with high percentage of edentulism, compromised functional oral status, and prosthetic needs. Mean intake of calorie and all nutrients were below the Recommended Nutrient Intake (RNI), while the prevalence of underweight was 25. 7o/o. There was a positive correlation between calorie intake and body mass index. Significant associations were noted between functional oral status with inadequate calorie intake and underweight among elderly Jiving in "Pondok" in Kelantan.